2022
DOI: 10.1002/jcsm.12953
|View full text |Cite
|
Sign up to set email alerts
|

ACSL4 contributes to ferroptosis‐mediated rhabdomyolysis in exertional heat stroke

Abstract: Background Rhabdomyolysis (RM) is a common complication of exertional heat stroke (EHS) and constitutes a direct cause of death. However, the mechanism underlying RM following EHS remains unclear. Methods The murine EHS model was prepared by our previous protocol. RNA sequencing is applied to identify the pathological pathways that contribute to RM following EHS. Inhibition of the acyl‐CoA synthetase long‐chain family member 4 (ACSL4) was achieved by RNA silencing in vitro prior to ionomycin plus heat stress e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 41 publications
(105 reference statements)
0
25
0
Order By: Relevance
“…The enzyme long-chain fatty acid CoA ligase 4 (LACS4) converts PUFAs to the acylated form and is considered to be a specific driver of ferroptosis, as its upregulation increases PUFA content in phospholipids and renders the cell more susceptible to ferroptosis 144 , 145 . Although an in-depth study into the role of LACS4 in cardiac muscle has not yet been conducted, this enzyme has been shown to be a novel therapeutic target for limiting skeletal muscle cell death and preventing rhabdomyolysis 146 .…”
Section: Molecular and Metabolic Drivers Of Ferroptosismentioning
confidence: 99%
“…The enzyme long-chain fatty acid CoA ligase 4 (LACS4) converts PUFAs to the acylated form and is considered to be a specific driver of ferroptosis, as its upregulation increases PUFA content in phospholipids and renders the cell more susceptible to ferroptosis 144 , 145 . Although an in-depth study into the role of LACS4 in cardiac muscle has not yet been conducted, this enzyme has been shown to be a novel therapeutic target for limiting skeletal muscle cell death and preventing rhabdomyolysis 146 .…”
Section: Molecular and Metabolic Drivers Of Ferroptosismentioning
confidence: 99%
“… 26 Another study with a sarcopenic mouse model suggested that iron overload upregulated p53 expression, thereby inhibiting the expression of SLC7A11, and ultimately leading to ferroptosis through LPO accumulation in skeletal muscle cells. 16 Ferroptosis has also been found to be involved in rhabdomyolysis caused by exertional heat stroke 27 and in atorvastatin-induced myopathy. 28 In our study, mRNA sequencing performed on skeletal muscles showed that the ferroptosis pathway was markedly enriched in COPD, accompanied by abnormal expression of Gpx4 and Ncoa4 .…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, iron chelators also have the ability to protect functional and histologic RM ( 132 ). Another previous study indicated the protective role of ACSL4 in mediating ferroptosis in the development of RM following EHS, which suggests that ACSL4 may also be a novel therapeutic target in RM ( 133 ). Overall, we point out that ferroptosis may play a vital role as a fundamental mechanism in a variety of MSKs ( Figure 6 ).…”
Section: Rhabdomyolysismentioning
confidence: 93%